Empowering Housewives' Entrepreneurship Through Makeup and Hijab Creative Training in an Effort Improving Economic Welfare - Trisnani Widowati; Anik Maghfiroh; Musdalifah Musdalifah; Wahyu Lestari; Milda Ruliyanti; Ikfina Kamal Ida; Lutfiah Khoirunnisa (Universitas Negeri Semarang, 2024)
This Community Service (PKM) activity aims to empower entrepreneurial skills in mothers in RW 06 Watusari Village, Pakintelan Village, Gunungpati District, Semarang in an effort to improve economic welfare. This service method is carried out by providing training and direct assistance to mothers in RW 06 Watusari Village, Pakintelan Village, Gunungpati District, Semarang on make-up and hijab creations. This service activity contributes to mothers in RW 06 Watusari Village, Pakintelan Village, Gunungpati District, Semarang, with materials presented by the service team and is expected to empower entrepreneurial skills as an effort to improve the family economy. With this service activity, it is hoped that mothers in RW 06 Watusari Village, Pakintelan Village, Gunungpati District, Semarang have make-up and hijab creation skills, which are expected to provide new ideas about entrepreneurship and be developed to improve the family economy. The output targets that can be produced from this activity are: 1) Participants in this Community Service activity have make-up and hijab creation skills., 2) Participants in the Community Service activity can empower their entrepreneurial skills. 3) Completion of Journal Articles Published in National Journals with ISSN, 4) News coverage of the implementation of community service activities in print or electronic media.